Techno-Economic Analysis on the Production of Copper Oxide (CuO) Nanoparticles by Hydrothermal Method on an Industrial Scale - Rahmi Sabila Sidqi; Rian Febriyana Putra; Clarysa Satari; Silmi Ridwan Putri; Asep Bayu Dani Nandiyanto (Urecol Journal. Part G: Multidisciplinary Research, 2021)
The purpose of this study was to evaluate the economic and technical layout carried out on industrial scale CuO production using the hydrothermal method. The evaluation method used is economic evaluation by calculating gross profit margin (GPM), payback period (PBP), break even point (BEP), internal rate return (IRR), cumulative net present value (CNPV), and profitability index (PI). CuO was synthesized using Cu(CH3COO)2.H2O dissolved in water and then 1M sodium hydroxide solution was added. The solution was put in an autoclave at 110?C for 2 hours. Distilled water and ethanol were used to wash the black precipitate obtained and dried at 90?C in air. The results of the calculation of GPM and CNPV from the manufacture of industrial scale CuO show that the payback period (PBP) has increased in the third year because the project has been running well. CuO applications on an industrial scale can be used as photocatalysts and lithium battery anodes. This research is expected to provide an industrial scale overview of the economic evaluation and layout of the production of CuO through the hydrothermal method used as a photocatalyst and anode of lithium-ion batteries.